The Contemporary Disease - Modifying Therapies in ALS: Clinical Evidence, Biomarkers, and Molecular Targets - Perz, Wiktor; Palacz, Bartosz; Kubiś, Natalia Marianna; Teper, Maria Magdalena; Polus, Aleksander; Wrona, Julia Anna; Gluzicka, Anna; Olczyk, Liwia; Piotrowski, Jędrzej; Korolchuk, Anhelina (Journal of Education, Health and Sport, 2026)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder characterized by progressive motor neuron loss and marked biological heterogeneity. Advances in molecular genetics and biomarker research have redefined ALS as a spectrum of molecularly distinct subtypes, creating new opportunities for disease-modifying therapeutic development. Aim To synthesize contemporary evidence on disease-modifying therapies in ALS, with a focus on clinical trial outcomes, validated biomarkers, and molecular targets that inform precision medicine approaches. Material and Methods This narrative review integrates peer-reviewed original studies, clinical trials, and highquality review articles published predominantly between 2017 and 2025. Literature was selected based on relevance to ALS molecular pathophysiology, targeted therapeutic strategies, biomarker development, and clinical trial methodology. Data were synthesized qualitatively, emphasizing target engagement, biomarker modulation, and translational limitations. Results ALS pathogenesis converges on shared downstream mechanisms, including RNA dysmetabolism, impaired proteostasis, mitochondrial dysfunction, and neuroinflammation, despite diverse genetic drivers. Antisense oligonucleotide (ASO) therapies - particularly targeting SOD1 - have demonstrated robust biological efficacy, including molecular target engagement and neurofilament light chain (NfL) modulation. NfL has emerged as the most robustly validated biomarker for prognosis, patient stratification, and pharmacodynamic assessment, although its predictive value for long-term clinical benefit remains under evaluation. Non–ASO disease-modifying approaches have shown variable clinical outcomes, highlighting methodological and biological challenges. Conclusions Disease-modifying intervention in ALS is biologically feasible but remains limited by delayed diagnosis, disease heterogeneity, and conventional trial design constraints.